Wideband and High-gain Metasurface-Based Circularly Polarized Antenna - Kedze, Kam Eucharist; Park, Ikmo (International Conference on Metamaterials, Photonic Crystals and Plasmonics, 2021)
A metasurface-based circularly polarized microstrip patch antenna with wide bandwidth and high gain is presented. The antenna structure is a square modified microstrip patch that is sandwiched between a metasurface and the ground plane. The metasurface comprises a 4 × 4 array of square patches, while the radiating microstrip patch has axial ratio (AR) tuning stubs and a cross slot. The microstrip patch and cross slot, in conjunction with the metasurface, generate multiple resonances and AR minimum points that are combined to produce large impedance, AR, and 3-dB gain bandwidths. The antenna with the dimensions of 54 mm × 54 mm × 3.1 mm has a -10 dB impedance bandwidth of 5.62-11.04 GHz (65.06%), a 3-dB AR bandwidth of 5.64- 7.89 GHz (33.25%), and a 3-dB gain bandwidth of 5.17-8.2 GHz (45.32%) with a peak gain of 12.17 dBic.